Antecedents and Consequences of Job Burnout among Human Resources Employee in Saudi Arbia - Naasani, Abdulmohsen A.; AlDawsari, Fatimah Faez (The Arab Journal of Administration, 2025)
Burnout has a negative impact not only on individuals but also on organizational outcomes’ efficiency and effectiveness, hence harming and threatening its survival. The study is conducted with the aim of investigating antecedents and consequences of job burnout among human resources employee in Saudi Arbia . Variables are job burnout workaholism, followed by job stress, emotional exhaustion, and turnover intention. Participants in this research were 206 employees working in Saudi Arabia. The data were collected by using an online questionnaire consisting of six sections and analyzed by SPSS. The results of the study show that job stress has a positive relation to job burnout and emotional exhaustion. Job burnout has positive impact to emotional exhaustion. Emotional exhaustion positively related to turnover intention. On the other hand, workaholism shows a negative relation with job burnout. 5 Hypothesis were developed to test the variables relation. moreover, implications would prove helpful to managers and HR professionals to understand the burnout behaviors of the HR employees in the workplace and adopt approaches and strategies to overcome burnout presently and for new era.